Práticas informacionais dos estudantes de medicina do internato da Universidade Federal de Ouro Preto em tempos de infodemia - Luciana de Oliveira (2024)
The contemporary era has been widely marked by the infodemic, a phenomenon defined as the excessive dissemination of information, often inaccurate or false, which characterizes misinformation, affecting various practices, particularly those in the healthcare field. In this context, this research aims to understand how the information practices of medical students at the Federal University of Ouro Preto are configured concerning the search, retrieval, selection, use, and sharing of information during internship in times of infodemic. The specific objectives seek to identify the sources of information used by medical students, the interference of the phenomena of infodemic, misinformation, and post-truth in information practices, in the development of clinical reasoning, and decision-making of medical students. The adopted approach is qualitative with descriptive characteristics. For data collection, the snowball technique was used. Based on the completion of 15 semi-structured interviews with the participants, Bardin's content analysis was applied for data categorization. The results of the interviews, as well as the investigated literature, indicate that the infodemic environment is a challenging factor that requires medical students to exercise critical thinking when choosing reliable sources of information. Additionally, a considerable influence of misinformation and post-truth was noted on the information practices of medical students who often make their clinical conduct choices based on their beliefs, values, and worldviews.